2018
DOI: 10.1080/10245332.2018.1498566
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cells and CD20+B cells in pediatric very severe aplastic anemia: possible clinical markers for evaluating the therapeutic efficacy and prognosis

Abstract: There is a moderate negative correlation between the percentage of Tregs and CD20 B cells in our study. Our results shed light on the roles of Tregs and CD20 B cells as therapeutic efficacy and prognostic markers of pediatric VSAA. Moreover, the mechanism underlying the decrease of blood Tregs and increase of CD20 B cells in pediatric VSAA patients have been discussed, indicating that Tregs may suppress B cell responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…In recent years, research on the roles of shikonin in human health has gradually deepened. Accumulating evidence suggests that shikonin can suppress tumor growth and overcome the resistance to chemotherapy drugs in tumor cells [10]. Tang et al [11] suggested that shikonin can significantly inhibit the proliferation of esophageal cancer cells by regulating the HIF1α/PKM2 signaling pathway.…”
Section: Mediators Of Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, research on the roles of shikonin in human health has gradually deepened. Accumulating evidence suggests that shikonin can suppress tumor growth and overcome the resistance to chemotherapy drugs in tumor cells [10]. Tang et al [11] suggested that shikonin can significantly inhibit the proliferation of esophageal cancer cells by regulating the HIF1α/PKM2 signaling pathway.…”
Section: Mediators Of Inflammationmentioning
confidence: 99%
“…We speculate that the changes in CTL function were due to shikonin-mediated inhibition of PKM2 levels in mDCs, which in turn regulated the expression of mDC costimulatory molecules and inflammatory factors. Recently, the role of Treg cell population in SAA pathogenesis has attracted much research attention [10]. Tregs are believed to control the progression of autoimmunity in AA by suppressing overactive T cells and preventing the antigen presentation process of mDCs [23].…”
mentioning
confidence: 99%
“…The most favored model is that of a dysregulated immune system leading to autoreactive T-cell destruction of hematopoietic stem and progenitor cells. This is well reflected in SAA patients with expanded CD8+ T-cells and increased TNFα and INFγ levels (17)(18)(19). However, the same immunological abnormality is rarely found in NSAA.…”
Section: Discussionmentioning
confidence: 92%